A designed magnetic CoFe2O4–hydroxyapatite core–shell nanocomposite for Zn(II) removal with high efficiency. Issue 5 (June 2015) - Foroughi, Firoozeh; Hassanzadeh-Tabrizi, S.A.; Amighian, Jamshid; Saffar-Teluri, Ali
Abstract: In this study, magnetic CoFe2 O4 –hydroxyapatite core–shell nanoparticles have been synthesized by reverse microemulsion method and used as adsorbent to remove Zn(II) from aqueous solution. The synthesized products were studied by X-ray diffraction, Brunauer–Emmett–Teller surface area analysis, vibrating sample magnetometer and transmission electron microscopy. The effect of parameters, including adsorbent dosage, contact time, and zinc concentration on the adsorption properties were investigated. The results revealed that hydroxyapatite was coated on the CoFe2 O4 surface and formed a core–shell structure. The adsorption of Zn(II) onto the nanoparticles increased sharply within 60 min and equilibrium condition can be obtained gradually. Adsorption data were well described by Freundlich model. The kinetic study illustrated that the adsorption of Zn(II) onto nanoparticles surface fits the pseudo-first-order model.